Characterization of a CsI(Tl)-SiPM detector to low energy protons for light dark matter search in a future Beam Dump eXperiment. (3rd March 2017) - Bondí, M.; Battaglieri, M.; Carpinelli, M.; Celentano, A.; Napoli, M. De; Vita, R. De; Leonora, E.; Marsicano, L.; Randazzo, N.; Sipala, V.
Abstract: The silicon Photomutiplier (SiPM) is a successful solid-state light detector. Thanks to its characteristics, especially the high quantum efficiency, comparable to that of PMTs, and the much higher gain compared to APDs, it can play an important role in many physics fields. For example a calorimeter read out by SiPMs is the proposed solution for the detection light dark matter in a future beam dump experiment. Although scintillating crystals coupled to SiPMs are widely used, they have been scarcely characterized as low energy ( ∼ MeV) ion detectors. In the present work we report a study of the light response of a large volume CsI(Tl) crystal, read out by a small area SiPM to low energy protons of different kinetic energies, from 2.5 MeV to 24 MeV . The results of the measurements allowed us to qualify the CsI(Tl)-SiPM solution in an unmeasured energetic regime.